1992
DOI: 10.1001/archsurg.1992.01420100094016
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial Comparing Two Methods of Fascia Closure Following Midline Laparotomy

Abstract: Three hundred forty women undergoing midline laparotomy were randomized into an interrupted suture (polyglactin 910, size 1) or a continuous suture (polyglyconate, size 0) closure group. The two groups were well balanced with respect to various risk factors for postoperative wound complications. Early evaluation revealed no differences between the continuous and interrupted suture groups with respect to wound infection (3% vs 1%), superficial wound dehiscence (2% vs 4%), and deep wound dehiscence (0.6% vs 0%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(38 citation statements)
references
References 12 publications
0
37
0
1
Order By: Relevance
“…However, since the introduction of synthetic absorbable sutures, the majority of these trials have shown no difference in the overall incidence of wound complications in comparison with various nonabsorbable sutures. At least four studies [9, 67, 68, 69]compared continuous versus interrupted closure of midline incisions. All found that continuous suture closure was as effective and as safe as interrupted suture closure with the advantage of being more expeditious.…”
Section: Wound-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the introduction of synthetic absorbable sutures, the majority of these trials have shown no difference in the overall incidence of wound complications in comparison with various nonabsorbable sutures. At least four studies [9, 67, 68, 69]compared continuous versus interrupted closure of midline incisions. All found that continuous suture closure was as effective and as safe as interrupted suture closure with the advantage of being more expeditious.…”
Section: Wound-related Factorsmentioning
confidence: 99%
“…However, PDS seems to be associated with a lower rate of IH [69, 70]. The double-stranded suture type providing nearly twice the initial tensile strength of a single strand of the same diameter may be valuable in high-risk patients (i.e., those having obesity) [70].…”
Section: Wound-related Factorsmentioning
confidence: 99%
“…These are also mechanic factors affecting wound healing. Wound infections of varying degrees affect the abdominal wall at different rates and they are major causes of development of incisional hernia or wound dehiscence (14,24,25). In our series, wound infection that was present in 69 patients (26%), had a significant relationship with incisional hernia (p=0.011) and wound dehiscence (p=0.001).…”
Section: Discussionmentioning
confidence: 57%
“…They recommended that closing midline abdominal fascial wounds with a running suture may be a superior method of closure in clean, incised wounds. Trimbos JB et al 13 in 1992 found that continuous closure of laparotomy wound was faster. They concluded that a running polyglyconate suture was better choice for closure of abdominal wall following midline laparotomy.…”
Section: Discussionmentioning
confidence: 99%